2021
DOI: 10.1016/j.ijid.2021.02.095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of influenza virus infection on pregnancy outcomes: A systematic review and meta-analysis of cohort studies

Abstract: Background: Adverse pregnancy outcomes are risk factors for neonatal mortality and morbidity. While some studies have demonstrated notable associations between influenza and adverse pregnancy outcomes, the findings have contrasted with other studies. This meta-analysis was conducted to assess the effect of influenza infection on pregnancy outcomes. Methods: We searched PubMed, Embase, Cochrane Library and Web of Science from inception to 4 November 2020. Relative risks (RRs) with 95% confidence intervals (CIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Based on the data discussed above, it is not surprising that several studies have reported increased risk of adverse pregnancy outcomes associated with influenza infection, but such findings were not confirmed by other studies (43). More specifically, it has been reported an increased occurrence of spontaneous miscarriage, preterm delivery, cesarean delivery, pneumonia, maternal hyperthermia, and post-partum hospital length of stay (43)(44)(45)(46). Similarly, the effects of maternal influenza infection on the fetus are also under investigation (43)(44)(45)(46), but evidence of the effects of inter-pandemic influenza on fetal outcomes has varied among different countries and the published studies have shown substantial biases (43).…”
Section: Influenza Virusmentioning
confidence: 90%
See 4 more Smart Citations
“…Based on the data discussed above, it is not surprising that several studies have reported increased risk of adverse pregnancy outcomes associated with influenza infection, but such findings were not confirmed by other studies (43). More specifically, it has been reported an increased occurrence of spontaneous miscarriage, preterm delivery, cesarean delivery, pneumonia, maternal hyperthermia, and post-partum hospital length of stay (43)(44)(45)(46). Similarly, the effects of maternal influenza infection on the fetus are also under investigation (43)(44)(45)(46), but evidence of the effects of inter-pandemic influenza on fetal outcomes has varied among different countries and the published studies have shown substantial biases (43).…”
Section: Influenza Virusmentioning
confidence: 90%
“…Based on the data discussed above, it is not surprising that several studies have reported increased risk of adverse pregnancy outcomes associated with influenza infection, but such findings were not confirmed by other studies (43). More specifically, it has been reported an increased occurrence of spontaneous miscarriage, preterm delivery, cesarean delivery, pneumonia, maternal hyperthermia, and post-partum hospital length of stay (43)(44)(45)(46).…”
Section: Influenza Virusmentioning
confidence: 95%
See 3 more Smart Citations